Energy harvesting from a bio cell. (February 2019) - Catacuzzeno, L.; Orfei, F.; Di Michele, A.; Sforna, L.; Franciolini, F.; Gammaitoni, L.
Abstract: This work shows experimentally how electrical energy can be harvested directly from cell membrane potential and used to power a wireless communication. The experiment is performed by exploiting the membrane potential of Xenopus oocytes taken from female frogs. Electrical potential energy of the membrane is transferred to a capacitor connected to the cell via a proper electrical circuit. Once the capacitor has reached the planned amount of energy, the circuit is disconnected from the cell and the stored energy is used to power a radio frequency communication that carries bio-sensed information to a distanced receiving circuit. Our result shows that electrical energy can be harvested directly from biological cells and used for a number of purposes, including wireless communication of sensed biological quantities to a remote receiving hub. Graphical abstract: Highlights: Biological cells are capable of providing a source of electrical energy. Experiments from a frog egg show that electrical energy can be harvested. Harvested energy from a bio cell can be used to perform micro scale activities. A wireless signal is sent at short distance using only the electrical energy from a bio cell.